A lignosulfonate-modified graphene hydrogel with ultrahigh adsorption capacity for Pb(ii) removal. Issue 30 (13th July 2016) - Li, Fengfeng; Wang, Xiluan; Yuan, Tongqi; Sun, Runcang
Abstract : A high capacity, low cost, eco-friendly and recyclable adsorbent, a lignosulfonate-modified graphene hydrogel, is successfully synthesized via a one-step method. Abstract : A lignosulfonate-modified graphene hydrogel (LS-GH) for Pb(ii ) adsorption was synthesized through a one-step method. The three-dimensional (3D) porous architecture of the graphene hydrogel was functionalized by using lignosulfonate with diverse oxygen containing groups. Benefiting from a large specific surface area, multiple porosity and sufficient active sites, the LS-GH adsorbent exhibited ultrahigh adsorption capacity (1210 mg g −1 ) for Pb(ii ) removal, which was among the highest of previously reported Pb(ii ) adsorbents. Importantly, the free-standing and flexible LS-GH can be used as a column-packed device, providing an efficient pathway for the fast removal of Pb(ii ) with an ultrahigh adsorption capacity of 1308 mg g −1 within 40 min. The high capacity LS-GH adsorbent is low cost, eco-friendly and recyclable, which could be an attractive adsorbent for the purification of wastewater on a large scale.